2022
DOI: 10.3390/ijerph191610034
|View full text |Cite
|
Sign up to set email alerts
|

Risk Associations between Vehicular Traffic Noise Exposure and Cardiovascular Diseases: A Residential Retrospective Cohort Study

Abstract: Environmental noise can induce detrimental health effects such as cardiovascular disease (CVD). The relationship between vehicular traffic noise pollution and CVD was investigated through a retrospective residential cohort study in the city of Pisa. Four exposure classes were defined for noise pollution, using noise propagation maps. The association between noise exposures and cause-specific mortality or hospitalization of the subjects of the cohort was calculated using the hazard ratio (HR) for night and day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Excluding one conference report, the overall RR per 10 dB L den was 1.03 (95 % CI: 1.00; 1.05), with significant heterogeneity between the studies. More recent findings, not included in the two reviews, also indicated lower risk estimates than in the WHO review or no clear associations [ [54] , [55] , [56] , [57] , [58] ]. All but one of these studies were strictly registry-based and did not contain any information on lifestyle, e.g., smoking, increasing the risk of residual lifestyle confounding compared to the studies in the two reviews, which generally included such data.…”
Section: Health Impact Of Transportation Noisementioning
confidence: 95%
See 1 more Smart Citation
“…Excluding one conference report, the overall RR per 10 dB L den was 1.03 (95 % CI: 1.00; 1.05), with significant heterogeneity between the studies. More recent findings, not included in the two reviews, also indicated lower risk estimates than in the WHO review or no clear associations [ [54] , [55] , [56] , [57] , [58] ]. All but one of these studies were strictly registry-based and did not contain any information on lifestyle, e.g., smoking, increasing the risk of residual lifestyle confounding compared to the studies in the two reviews, which generally included such data.…”
Section: Health Impact Of Transportation Noisementioning
confidence: 95%
“…However, it should be noted that simplified noise exposure assessment approaches were applied in the studies which found no association. In studies with less complete confounder adjustment, two studies reported an association with stroke [ 56 , 78 ], whereas three other studies did not [ 54 , 58 , 79 ].…”
Section: Health Impact Of Transportation Noisementioning
confidence: 99%
“…each subject can enter the cohort at different times during the study period considering birth and migration movements. Regarding hospital admissions, we used the methodology also reported in an our previous study [ 18 ], i.e. for each hospitalization cause, the calculation of person years (py) concerned the period from the entry in the cohort until the first admission for that cause.…”
Section: Methodsmentioning
confidence: 99%
“…It has been established that low-frequency noise can have a harmful effect not only on hearing, but also on other human systems, and its biological effect is similar to the effect of infrasound on a person. Therefore, studies are needed to clarify the nature of the frequency dependence of biological effects on the conditional boundary between the infrasonic and sonic ranges [24,[26][27][28].…”
Section: Means Of Measurement and Hygienic Regulation Of Industrial A...mentioning
confidence: 99%